2003
DOI: 10.1017/s1041610203008767
|View full text |Cite
|
Sign up to set email alerts
|

Case Series With Late-Onset Psychosis Hospitalized in a Geriatric Psychiatry Unit in Turkey: Experience in 9 Years

Abstract: In this article we report the first series of Turkish inpatients with late-onset psychosis, and describe our 9-year experience at the only inpatient geriatric psychiatry department in Turkey. Among 420 patients hospitalized between 1993 and 2002, 27 were psychotic. In this group, eight patients were diagnosed as having late-onset schizophrenia (LOS) and six very-late-onset schizophrenia-like psychosis (VLOSLP). Five patients had early-onset schizophrenia and eight had delusional disorder. Females were more fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…Some authors reported formal thought disorders in 100% of French-speaking VLOSLP patients [25], while other authors working mostly on English-and Deutsch-speaking patients reported a low prevalence [18], and a lower risk of formal thought disorder in VLOSLP than in EOS patients [14]. Formal thought disorder was found to be absent in VLOSLP patients in the remaining studies [20,24].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Some authors reported formal thought disorders in 100% of French-speaking VLOSLP patients [25], while other authors working mostly on English-and Deutsch-speaking patients reported a low prevalence [18], and a lower risk of formal thought disorder in VLOSLP than in EOS patients [14]. Formal thought disorder was found to be absent in VLOSLP patients in the remaining studies [20,24].…”
Section: Introductionmentioning
confidence: 93%
“…However, in most studies, negative symptoms were absent in VLOSLP [14,20] while they were present in EOS and to a lesser extent in LOS [14]. Negative symptoms were not at all or barely mentioned in several studies on VLOSLP [18,21,24,26].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…1 As well, the diagnostic criteria proposed by the International Late-Onset Schizophrenia Group were not clearly outlined, 1 which has led to variable use of this term. 9,10,26,27 Subsequent studies directly comparing these proposed age categories on clinical and epidemiological aspects were equivocal. 9 In the current psychiatric diagnostic systems (DSM-V, ICD-10), schizophrenia and delusional disorder is only diagnostically allowed, and age-specific diagnostic terms are not included in DSM-V 24 or ICD-10.…”
Section: History Of Late-onset Psychotic Disordermentioning
confidence: 99%